faktor-faktor yang mempengaruhi audit delay pada perusahaan gopublic di indonesia - mega panorama; muhammad nuryatno (Jurnal Akuntansi, 2019)
The main objective of this study is to detect whether company size, profitability, company age, and solvency influence audit delay. Random effect model is used for this study. The sample companies involved in this study were obtained from surveys of public companies in the LQ-45 registered on the Indonesian stock exchange. The data covers a five-year period from 2013 to 2017. The results show that the age of the company has a significant influence on audit delay and profitability which has a significant influence on audit delay while the age of the company and solvency does not affect audit delay